CARE SYSTEMS IN MOTOR VEHICLES IN THE CAR & MOTOR SAVE WITH COMPUTERIZED - Siswono Siswono; Jalinas, Ir, MM Jalinas, Ir, MM (Jurnal Sistem Informasi, 2000)
Computerized system in a company vehicle, especially at daycare C & M Save this, itcan generate more accurate reports, save time, no errors transaction data, consumerdata search easier, and also provide greater benefits compared with manual recording.